Context Overview of Empowering Women's in Uzbekistan - Kuchkarova Yana Davidovna; Abduvaliyeva Diyora (Indonesian Journal Publisher, 2025)
The article investigates the women's context in Uzbekistan focusing on academic and professional support along with obstacles they meet during their careers. It discusses the government support women receive and the cultural as well as social barriers they encounter on their journey. The authors present governmental regulations and their implication in the real life. The authors state that Uzbekistan has made commendable advances in the pursuit of gender equality in higher education though the journey is far from complete